Análise e projeto do reator eletrônico auto-oscilante para reconhecimento de lâmpadas fluorescentes - Lopes, Juliano de Pelegrini (2014)
This work presents the analysis and design of the self-oscillating electronic ballast to fluorescent lamps detection. The electronic ballast must be able to detect and run lamps with different power ratings, according to the fluorescent lamps control standards. A SEPIC converter is used to perform power factor correction and a half-bridge inverter supplies the lamps. An analog circuit must detect the lamp and set its operation power. The main feature of the proposed electronic ballast is use the self-oscillating gate driver circuit in the SEPIC and half-bridge command circuits. Experimental results presented show the feasibility of the proposed solution. The electronic ballast meets the electrode preheating and harmonic currents injected into the public supply system standards. An analysis of fluorescent lamps detection methods with the self-oscillating gate driver circuit and its simulation results are presented.